Prognostic Impact of Right Ventricular Damage Markers on CT in Patients Undergoing TAVI - Baris, Veysel Ozgur; Karaca, Ozkan; Harman, Murat; Poyraz, Fatih; Koksal, Fatma; Ozturk, Alperen; Kobat, Mehmet Ali (Mdpi, 2025)
Background: In patients undergoing surgical aortic valve replacement due to severe aortic valve stenosis (AS), the presence of right ventricular damage markers (RVDMs) determined by echocardiography is a poor prognostic indicator. However, such data is not available in patient groups who have undergone transcatheter aortic valve replacement (TAVI). The aim of this study is to investigate the prognostic value of RVDM determined by computed tomography (CT) in a patient group undergoing TAVI. Material and Method: This multicentre, prospective study included 184 patients who underwent TAVI. In basal CT, the pulmonary artery (PA) diameter and right ventricular outflow tract myocardial thickness (RVOTMT) in mid-systole and maximal right and left ventricular diameter (RVD/LVD) ratios in mid-diastole were measured as indicators of RVDM before the TAVI procedure. The primary endpoint of the study was 1-year mortality. Results: The primary endpoint of the study was observed in 42 patients (22%). Among the CT parameters, the PA diameter, RVOTMT, and maximal RVD/LVD ratio were observed to be higher in the mortality group (p < 0.001). In the ROC analysis, a PA diameter of 30.5 and above had a 78% sensitivity and 82% specificity (AUC: 0.87 95% CI 0.82-0.93, p < 0.001), an RVOTMT of 4 mm and above had 90% sensitivity and 87% specificity (AUC: 0.93 95% CI 0.87-0.99, p < 0.001), and a maximal RVD/LVD ratio of 0.91 and above showed 90% sensitivity and 92% specificity (AUC: 0.94 95% CI 0.89-0.99, p < 0.001) to predict one-year mortality. In the Cox regression analysis, the RVOTMT and maximal RVD/ LVD ratios were found to be the best independent parameters showing 1-year mortality. Conclusion: This study showed that RVDMs determined by CT are strong predictors of 1-year mortality in severe AS patients treated with TAVI.
Keywords: TAVI; CT; mortality; prognostic marker